High-mobility group box 1 in acute kidney injury - Li, Xuan; Jing, Guilin; Guo, Zhentao; Guo, Zhaoan (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) remains a major clinical concern owing to its association with elevated morbidity and mortality. The nuclear protein high-mobility group box protein 1 (HMGB1), recognized for its evolutionary conservation, has emerged as a key mediator in AKI pathogenesis. Upon cellular injury, HMGB1 translocate into the extracellular space, where it operates as a damage-associated molecular patterns molecule. Its release intensifies inflammatory responses, exacerbates oxidative stress, and triggers ferroptosis. Furthermore, HMGB1 engages receptors such as TLRs and RAGE, ultimately contributing to various forms of regulated cell death. This review comprehensively summarizes the biological characteristics, regulatory mechanisms, and pathological roles of HMGB1 in AKI. It highlights HMGB1’s central role in sepsis-associated AKI, ischemia-reperfusion injury, cisplatin-induced nephrotoxicity, and contrast-induced nephropathy. Moreover, HMGB1 demonstrates promising potential as a diagnostic and prognostic biomarker due to its early release and strong correlation with disease severity and outcomes. Targeting HMGB1 through natural compounds, small molecules, microRNAs, or specific antibodies shows therapeutic promise in preclinical models by attenuating inflammation, oxidative damage, and cell death. Future studies focusing on clinical validation and combination strategies may further establish HMGB1 as a diagnostic, prognostic, and therapeutic target, providing new avenues for improving AKI management and patient outcomes.